2015
DOI: 10.1007/s11356-015-5788-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term radionuclide and heavy metal contamination on the activity of microbial communities, inhabiting uranium mining impacted soils

Abstract: Ore mining and processing have greatly altered ecosystems, often limiting their capacity to provide ecosystem services critical to our survival. The soil environments of two abandoned uranium mines were chosen to analyze the effects of long-term uranium and heavy metal contamination on soil microbial communities using dehydrogenase and phosphatase activities as indicators of metal stress. The levels of soil contamination were low, ranging from 'precaution' to 'moderate', calculated as Nemerow index. Multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…It is noted that long-term exposure of microbial communities to heavy metals can influence their tolerance and adaptation to soil contamination. Soil organic matter is considered the main factor for high microbial enzyme activities in such soils and mitigation of heavy metal toxicity [42].…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that long-term exposure of microbial communities to heavy metals can influence their tolerance and adaptation to soil contamination. Soil organic matter is considered the main factor for high microbial enzyme activities in such soils and mitigation of heavy metal toxicity [42].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the microbial community may adapt to the heavy metal concentrations overcoming the negative effects of contamination [52][53][54]. None of the microbial parameters (biomass, respiration or respiratory quotient, or diversity) were correlated to the gradient in heavy metals of ultramafic soils, suggesting adaptation by the microbial community to the stress imposed by edaphic conditions [12].…”
Section: Discussionmentioning
confidence: 99%
“…None of the microbial parameters (biomass, respiration or respiratory quotient, or diversity) were correlated to the gradient in heavy metals of ultramafic soils, suggesting adaptation by the microbial community to the stress imposed by edaphic conditions [12]. Some studies showed microbial tolerance and adaptation to soil contamination due to the long-term metal exposure and indicated that soil organic matter is a key factor in maintaining high microbial enzyme activities and mitigating metal toxicity [53]. In general, microorganisms from serpentine soils showed a high level of tolerance to trace metals, such as Ni, Co, and Cr.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on microbial resistance to toxic metals do not specify whether the tolerance of microorganisms is due to physiological acclimation (during exposure to the metals), or due to adaptation involving a genetically‐based resistance . Adaptation and acclimation of microorganisms to heavy metals have recently been investigated by various researchers indicating the important focus of this research.…”
Section: Introductionmentioning
confidence: 99%